2014
DOI: 10.5539/ijef.v6n12p148
|View full text |Cite
|
Sign up to set email alerts
|

Degree of Operating Leverage, Contribution Margin and the Risk-Return Profile of Emerging Companies: Evidence from Nigeria

Abstract: This article investigates the effects of degree of operating leverage and contribution margin on profitability and risk of Nigeria's emerging companies. Emerging companies were described in this study as small and medium-sized enterprises that are high-potential and high-growth in character listed in the Nigerian Stock Exchange's Alternative Investment Market. Cross-sectional and time series data were collected from Nigerian Stock Exchange for the top ten emerging companies listed in the market. Additional res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
(7 reference statements)
1
4
0
1
Order By: Relevance
“…Similarly, García-Feijóo and Jansen (2020) provide evidence that operating leverage is positively associated with monthly stock returns in a sample of firms in 20 developed countries. Dagogo (2014) studied the impact of operating leverage on the risk and profitability of Nigerian emerging firms. The results of this study indicated that operating leverage has insignificant effect on operating profitability and operating risk.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, García-Feijóo and Jansen (2020) provide evidence that operating leverage is positively associated with monthly stock returns in a sample of firms in 20 developed countries. Dagogo (2014) studied the impact of operating leverage on the risk and profitability of Nigerian emerging firms. The results of this study indicated that operating leverage has insignificant effect on operating profitability and operating risk.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Chen et al (2019) find that operating leverage has positive effect on profitability, whereas Zabolotnyy and Wasilewski (2018) show a negative relationship between operating leverage and profitability. Moreover, Dagogo (2014) and Khan et al (2017) document insignificant relationship. The reasons for these contradictory findings may be due to previous studies being performed in different institutional and economic environments.…”
Section: Introductionmentioning
confidence: 98%
“…We compute Tobin's Q as Total Book Value of Assets minus Book Value of Equity plus Market Value of Assets divided by Total Book Value of Assets. while the commodity price and exchange rate proxied by the regression coefficient of the influence of commodity price and exchange rate fluctuations on stock returns,this is follows methology byHaushalter et al2002;Jin and Jorion, 2006;Bodnar and Wong 2003.To gauge investment,we use proxied by the ratio of Capital Expenditure to Book Value of Assets (CAP/BVA), and risk business proxied by Degree Operating Leverage (DOL) as used by previous researchers (Dagogo, 2014;Gritta, 2003, Gahlon andGentry 1982).…”
Section: Figure 1path Analysis Model Theinfluence Of Commodity Pricementioning
confidence: 99%
“…(i) La determinación del punto de equilibrio (P. E.), que empleó un indicador y consiste en igualar el nivel de ingresos al de los costos, usando como referencia de análisis una hectárea de cafetal. Para ello, se utilizó el método del margen de contribución (Dagogo, 2014), que permite determinar el punto de equilibrio en unidades (P. E. U.)…”
Section: Análisis De La Rentabilidadunclassified